COVID-19 in Relation to Hyperglycemia and Diabetes Mellitus - Al-kuraishy, Hayder M.; Al-Gareeb, Ali I.; Alblihed, M.; Guerreiro, Susana G.; Cruz-Martins, Natália; Batiha, Gaber El-Saber (Frontiers in Cardiovascular Medicine, 2021)
Coronavirus disease 2019 (COVID-19), triggered by the severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) may lead to extra-pulmonary manifestations, like diabetes mellitus (DM) and hyperglycemia, both predicting a poor prognosis and an increased risk of death. SARS-CoV-2 infects pancreas through angiotensin-converting enzyme 2 (ACE2) where it is highly expressed compared to other organs, leading to pancreatic damage with subsequent impairment of insulin secretion and development of hyperglycemia even in non-DM patients. Thus, this review aims provides an overview on the potential link between COVID-19 and hyperglycemia as a risk factor for DM development in relation to DM pharmacotherapy. Data obtained underline that SARS-CoV-2 infection in DM patients is more severe and associated with poor clinical outcomes, as a result of the presence of preexistent co-morbidities and hyper-inflammation. SARS-CoV-2 infection impairs glucose homeostasis and metabolism in DM and non-DM patients due to cytokine storm (CS) development, down-regulation of ACE2 and direct injury of pancreatic β-cells. Therefore, up-regulation of ACE2 by diabetic pharmacotherapy, such as metformin, SGLT2 inhibitors and pioglitazone may improve the clinical outcomes in mild-to-moderate COVID-19 patients with DM. Nevertheless, insulin therapy is recommended in severe COVID-19 patients with DM for a strict control of blood glucose and to avoid the occurrence of DKA by metformin and SGLT2 inhibitors. In short, insulin therapy is more effective than other anti-DM pharmacotherapy in the management of COVID-19 DM patients due to low risk of uncontrolled hyperglycemia and DKA. As well, insulin has pleiotropic effect independent of glucose-lowering effect through amelioration of COVID-19-induced CS